An integrated digital PCR system with high universality and low cost for nucleic acid detection - Wang, Kangning; Li, Bin; Guo, Yu; Wu, Yanqi; Li, Yan; Wu, Wenming (Frontiers in Bioengineering and Biotechnology, 2022)
Digital PCR is the most advanced PCR technology. However, due to the high price of the digital PCR analysis instrument, this powerful nucleic acid detection technology is still difficult to be popularized in the general biochemistry laboratory. We built a low-cost digital PCR system. This system only relies on low-cost traditional flat PCR equipment to provide temperature conditions for commercialized dPCR chips, and House-made fluorescence detection system is designed and optically optimized to meet a wide range of reagent requirements. One of the biggest disadvantages of traditional commercialized digital PCR system is the poor universality of reagents: each instrument can only be used for a few customized kits. By contrast, our system not only has a low cost (< 8000 US dollars), but also has a much higher universality for nucleic acid detection reagents than the traditional commercial digital PCR system. In this paper, several samples were tested. The genes used in the experiment were plasmids containing UPE-1a fragment, TP53 reference DNA, Hepatitis B Virus DNA, Leukemia sample, SARS-COV-2 DNA, and SARS-COV-2 RNA. Under the condition that DNA can be amplified normally, the function of dPCR system can be realized with simpler and low-price equipment. This makes the whole system smaller, easier to operate and cheaper. For the commercial dPCR system, in the experiment, some DNA cannot be detected because of the special formula when it is configured as the reaction solution, but these DNA fluorescence signals can be clearly detected by our system, and the concentration can be calculated. Our system is more applicable than commercial dPCR system to form a new dPCR system that is smaller and more widely applicable than commercially available machinery.